Antibacterial interactions, anti-inflammatory and cytotoxic effects of four medicinal plant species - Refilwe G. Kudumela; Lyndy J. McGaw; Peter Masoko (BMC, 2018)
Abstract Background The constant emergence of antibiotic resistant species and the adverse side effects of synthetic drugs are threatening the efficacy of the drugs that are currently in use. This study was aimed at investigating the possible antibacterial interactions, anti-inflammatory and cytotoxic effects of selected medicinal plants based on their traditional usage. Methods The acetone extracts of four plant species were assessed independently and in combination for antibacterial activity using microdilution assay and the sum of the fractional inhibitory concentration (FIC) was calculated. The ability of Dombeya rotundifolia and Schkuhria pinnata extracts to inhibit the production of reactive oxygen species (ROS) in LPS induced RAW 264.7 macrophage cells was evaluated using Dichloro-dihydro-fluorescein diacetate (H2DCF-DA) assay to determine anti-inflammatory potential and the toxicity on African green monkey kidney (Vero) cells was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Results The antibacterial efficacies of the different combinations of Schkuhria pinnata (A), Commelina africana (B), Dombeya rotundifolia (C) and Elephantorrhiza elephantina (D) plants varied from combination to combination. Synergistic effects were only exhibited against P. aeruginosa, while the antagonistic effects were only observed against E. coli. Both S. pinnata and D. rotundifolia demonstrated anti-inflammatory potential by inhibiting the production of ROS in a dose dependant manner. The cytotoxicity of the plants (LC50 values) ranged from < 25.0 to 466.1 μg/mL. S pinnata extract was the most toxic with the lowest LC50 value of < 25.0 μg/mL. Conclusions The synergistic interaction observed indicates that combinational therapy may improve biological activity. This report highlights the anti-inflammatory potential of S. pinnata and D. rotundifolia; which could be exploited in the search for anti-inflammatory agents. However, the cytotoxicity of S. pinnata highlights the importance of using this plant with caution.